A pilot study on the allergen-specific IgE to molecular components on polysensitized mite allergic asthmatic patients in Guangzhou, China. (January 2019) - Hu, Haisheng; Luo, Wenting; Wu, Zehong; Cai, Chuanxu; Huang, Huimin; Sun, Baoqing
Highlights: The sensitization of 112 allergen components among mite allergic polysensitized asthmatic patients from southern China. Sensitization to rDer p 10 was correlated to food allergy in mite allergic polysensitized asthmatic patients. Positive rate to nPhl p 4 was significantly higher in the patients with AA + AR than those with AA only. Singleplex ImmunoCAP usually detect more positive cases than ISAC. Abstract: Objective: Using multiplex microarray-based component resolved diagnosis (CRD) to investigate the allergen sensitization profile of allergic asthma patients in southern China. Method: Serum samples from 57 polysensitized mite allergic asthmatic patients in a tertiary referral centre of southern China were tested with multiplex CRD (ISAC) for specific immunoglobulin E (sIgE) against 112 single allergen and components. Result was then compared with those from singleplex ImmunoCAP. Results: With ISAC, the highest sensitization was seen for nDer f 1 (71.9%), rDer f 2 (73.7%), nDer p 1 (70.2%) and rDer p 2 (66.7%), whereas rDer p 10 and other storage mites' components only showed 10% positivity. rFel d 1 and rCan f 1 were found positive in 29.8% and 14.0% samples respectively. Other epithelia components had less than 7.0% positive rate. Sensitization to pollen components was dominated by nCyn d 1 (17.5%) and nPhl p 4 (12.3%), Carbohydrate cross-reactive determinants (CCD) was positive in 4 patients who were also positive to nPhl p 4, nCyn d 1 and rPla a 2, and all of them have combined asthma and rhinitis. The sensitivity to mold (rAsp f 3), cockroach (nBla g 7) and Anisakis simplex component (rAni s 3) were all the same at 8.8%. 93.0% patients were sensitive to more than one component, with more than half of them (57.9%) positive to five or more components. Patients with combined asthma and rhinitis (AA + AR) were sensitive to more components than those with asthma only (AA). Positive rate to nPhl p 4 was significantly higher in patients with AA + AR than with AA only ( χ 2 = 4.31, P = 0.038). Compared with ImmunoCAP, ISAC showed a similar high detection rate for D. pteronyssinus and D. farinae, but only 10.0% of B. tropicalis sensitive patients were positive to rBlo t 5. Optimal scale analysis on correlation of allergens components showed rDer p 10 was associated to food allergy. Conclusion: Being the first multiplex microarray based CRD study on southern Chinese, ISAC showed house dust mites components were the major allergen components led to sensitization in asthmatic patients. Patients with combined AA + AR were sensitive to more components than those with AA only. Other components with higher positive rate include pollen components nCyn d 1, nPhl P 4 and animal dander components rFel d 1 and rCan f 1. For B. tropicalis, the rBlo t 5 in ISAC may not represent the major Blomia component in southern Chinese patients.